Study protocol for Running for health (Run4Health CP): a multicentre, assessor-blinded randomised controlled trial of 12 weeks of two times weekly Frame Running training versus usual care to improve cardiovascular health risk factors in children and youth with cerebral palsy. Issue 4 (29th April 2022) - Reedman, Sarah E; Sakzewski, Leanne; McNamara, Lynda; Sherrington, Catherine; Beckman, Emma; West, Kerry; Trost, Stewart G; Thomas, Rachel; Chatfield, Mark D; Dutia, Iain; Gennen, Alix; Dodds, Bridget; et al.
Abstract : Introduction: Children and youth with moderate-severe (Gross Motor Function Classification System (GMFCS) levels II–V) cerebral palsy (CP) participate less frequently in physical activities compared with peers without CP and have elevated risk of cardiorespiratory morbidity and mortality in adulthood. Frame Running (RaceRunning) is a new athletics discipline that is an accessible option for physical activity participation for people with moderate-severe CP. There is no high-quality evidence for the effect of Frame Running on cardiovascular disease in children and young people with CP. The primary aim of this study is to conduct a randomised controlled trial of the effect of 12 weeks of Frame Running training on risk factors for cardiovascular disease. Methods and nalysis: Sixty-two children and youth with CP (age 8–20 years) in GMFCS levels II–V will be recruited across four sites and randomised to receive either 12 weeks of Frame Running training two times weekly for 60 min, or usual care. Outcomes will be measured at baseline, immediately postintervention (primary endpoint) and 12 weeks later for retention of training effects. The primary outcome is cardiorespiratory fitness as measured by distance covered on Six Minute RaceRunner Test with 1 min heart rate recovery. Other outcomes include blood pressure, objectively measured physical activity, body mass index, waist circumference, percentage body fat, gross motor function capacity, community participation, feasibility, tolerability and safety. Adverse events will be monitored, and participants and their caregivers will be interviewed to discern their experiences of participation in Frame Running. Ethics and dissemination: The Children's Health Queensland Hospital and Health Service and the University of Queensland Human Research Ethics Committees have approved this study. Results will be disseminated in peer-reviewed journals and scientific conferences; through professional and athletic organisations; and to people with CP and their families. Trial registration number: ACTRN12621000317897; Australian New Zealand Clinical Trials Registry number.